A Comparison of Two Ambulatory Blood Pressure Monitors Worn at the Same Time. Issue 5 (8th April 2013) - Kallem, RadhaKrishna R.; Meyers, Kevin E.C.; Sawinski, Deirdre L.; Townsend, Raymond R.
<x xml:space="preserve">Abstract</x> There are limited data in the literature comparing two simultaneously worn ambulatory blood pressure (BP) monitoring (ABPM) devices. The authors compared BPs from two monitors (Mobil‐O‐Graph [I.E.M., Stolberg, Germany] and Spacelabs 90207 [Spacelabs Medical, Issequah, WA]). In the nonrandomized component of the study, simultaneous 8‐hour BP and heart rate data were measured by Mobil‐O‐Graph, consistently applied to the nondominant arm, and Spacelabs to the dominant arm on 12 untreated adults. Simultaneous 8‐hour BP and heart data were obtained by the same monitors randomly assigned to a dominant or nondominant arm on 12 other untreated adults. Oscillometric BP profiles were obtained in the dominant and nondominant arms of the above 24 patients using an Accutorr (Datascope, Mahwah, NJ) device. The Spacelabs monitor recorded a 10.2‐mm Hg higher systolic pressure in the nonrandomized (P=.0016) and a 7.9‐mm Hg higher systolic pressure in the randomized studies (P=.00008) compared with the Mobil‐O‐Graph. The mean arterial pressures were 1 mm Hg to 2 mm Hg different between monitors in the two studies, and heart rates were nearly identical. Our observations, if confirmed in larger cohorts, support the concern that ABPM device manufacturers consider developing normative databases for their devices.